Agent-based simulation study of the intra-urban discontinuity effects in Delhi on dispersal of Aedes aegypti mosquitoes, vector of dengue, chikungunya and Zika viruses - Somsakun Maneerat; Éric Daudé (Cybergeo, 2017)
In order to fight against the transmission of dengue, yellow fever, chikungunya and Zika viruses, significant resources were allocated to the process of restricting the propagation of their main vector, the Aedes aegypti mosquito. Research on this mosquito’s living areas is thus necessary to characterize more precisely the areas that need to be monitored and treated. An alternative to field surveys consists of evaluating the characteristics of these living areas through spatialized models. It is in this context that we developed the simulation model MOMA (Model Of Mosquito Aedes aegypti), an agent-based model which integrates a vast set of biological and behavioral knowledge about the mosquito in a simulation environment based on the needs and constraints specific to Aedes aegypti. In this paper, we present MOMA and a study of the effects of local configurations on the dispersion capacity of mosquito cohorts. The simulations in this study were carried out using data from an urban neighborhood in the city of Delhi (India). This virtual laboratory, constructed in collaboration with entomologists, thus makes it possible to represent the mosquito’s living areas, which are either restricted or facilitated by spatial amenities conditioning its needs and its capacity of movement during its lifetime.Keywords: dengue, health, agent-based model, risk, urban area, modeling/modelling